Non-HDL-cholesterol in dyslipidemia: Review of the state-of-the-art literature and outlook - Raja, Vikrama; Aguiar, Carlos; Alsayed, Nasreen; Chibber, Yogeyaa S.; ElBadawi, Hussein; Ezhov, Marat; Hermans, Michel P.; Pandey, Ramesh Chandra; Ray, Kausik K.; Tokgözoglu, Lale; Zambon, Alberto; Berrou, Jean-Pascal; et al. (Atherosclerosis, 2023)
Dyslipidemia refers to unhealthy changes in blood lipid composition and is a risk factor for atherosclerotic cardiovascular diseases (ASCVD). Usually, low-density lipoprotein-cholesterol (LDL-C) is the primary goal for dyslipidemia management. However, non-high-density lipoprotein cholesterol (non-HDL-C) has gained attention as an alternative, reliable goal. It encompasses all plasma lipoproteins like LDL, triglyceride-rich lipoproteins (TRL), TRL-remnants, and lipoprotein a [Lp(a)] except high-density lipoproteins (HDL). In addition to LDL-C, several other constituents of non-HDL-C have been reported to be atherogenic, aiding the pathophysiology of atherosclerosis. They are acknowledged as contributors to residual ASCVD risk that exists in patients on statin therapy with controlled LDL-C levels. Therefore, non-HDL-C is now considered an independent risk factor or predictor for CVD. The popularity of non-HDL-C is attributed to its ease of estimation and non-dependency on fasting status. It is also better at predicting ASCVD risk in patients on statin therapy, and/or in those with obesity, diabetes, and metabolic disorders. In addition, large follow-up studies have reported that individuals with higher baseline non-HDL-C at a younger age (<45 years) were more prone to adverse CVD events at an older age, suggesting a predictive ability of non-HDL-C over the long term. Consequently, non-HDL-C is recommended as a secondary goal for dyslipidemia management by most international guidelines. Intriguingly, geographical patterns in recent epidemiological studies showed remarkably high non-HDL-C attributable mortality in high-risk countries. This review highlights the independent role of non-HDL-C in ASCVD pathogenesis and prognosis. In addition, the need for a country-specific approach to dyslipidemia management at the community/population level is discussed. Overall, non-HDL-C can become a co-primary or primary goal in dyslipidemia management. [Display omitted] •Non-HDL-C is a consistent and reliable residual risk predictor of ASCVD and all non-HDL-C contributing lipoproteins independently promote ASCVD.•Non-HDL-C is recommended as a co-primary treatment goal, particularly for high-risk patients.•The reliability of measuring non-HDL-C in a non-fasting state adds to its ease of use.•Baseline non-HDL-C levels <45 yrs. are predictive of CVD events at a later age.•There is an intriguing geographical pattern in non-HDL-C levels and related mortality.